1987
DOI: 10.1108/eb022645
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Collaboration: Facilitating Cooperative Work Through Communication

Abstract: The System Concepts Laboratory (SCL) of Xerox PARC is in the second year of a research program investigating the support and enhancement of collaboration. To begin, we explain our research goals and operationally define “collaboration” as we have chosen to study it. Then, we describe the environment in which the research takes place, including the two‐site, distributed organization of SCL. In our first year, we have had many experiences that are relevant to understanding collaboration and we present a few of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…More recent studies of video networks in R&D organizations [1,4,9,10] have illustrated the value of video communication networks, as well as showing some of their limitations.…”
mentioning
confidence: 98%
“…More recent studies of video networks in R&D organizations [1,4,9,10] have illustrated the value of video communication networks, as well as showing some of their limitations.…”
mentioning
confidence: 98%
“…In our own academic department, as well as in other research settings [6] [7], a great deal of work i s a c c o m p l i s h e d t h r o u g h t h i s t y p e o f i n f o r m a l communication [14]. While meetings and courses make it difficult to catch up with students and faculty, deviations from the schedule outlined on a public calendar exacerbate the problem.…”
Section: Informal Communicationmentioning
confidence: 99%
“…While the technology had only mixed success in supporting these information transfer and diagnosis tasks, Rocknff [21, p. 1087] offers a "clinical impression that this technology improves the cohesiveness and sense of organizational unity experienced by health care providers in a geographically dispersed system (i.e., it facilitates their functional integration)." More recent studies of video networks in R&D organizations [2,3,7,8,17] have illustrated the value of video communication networks, as well as showing some of their limitations. For example, the Xerox PARC experiment described earlier stiggests that a video link can be barely adequate to promote a shared context and culture to support joint work across two R&D locations, but that audio and video alone will be insufficient for accomplishing tasks.…”
Section: Richness and Social-orientation Of In-mentioning
confidence: 99%
“…Recent studies of encounters across video conferencing systems show that these systems can lead to spontaneous interaction, although less than in face-to-face settings [7]. A recent demonstration project at Xerox PARC provided a continuous video and audio connection between two of its research facilities located hundreds of miles apart [2,8]. Usage data indicated that over 70% of the interpersonal communication between the two sites consisted of short, casual, "drop-in" interactions and that most of these interactiotis would not have occurred without a continuous video link.…”
mentioning
confidence: 99%